1995
DOI: 10.1007/bf00051578
|View full text |Cite
|
Sign up to set email alerts
|

Influence of external factors on secondary embryogenesis and germination in somatic embryos from leaves of Quercus suber

Abstract: Somatic embryogenesis was obtained in cultures of leaves from young seedlings of Quercus suber L. A twostage process, in which benzyladenine and naphthaleneacetic acid were added first at high and then at low concentrations, was required to initiate the process. Somatic embryos arose when the explants were subsequently placed on medium lacking plant growth regulators. The embryogenic lines remained productive, by means of secondary embryogenesis, on medium without growth regulators. However, this repetitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 29 publications
3
34
0
3
Order By: Relevance
“…Nevertheless, embryo dormancy and immaturity problems needed to be overcome. Osmoticum (high sucrose concentration) and chilling treatments had been tested in order to promote germination of cork oak somatic embryos (Fernández-Guijarro et al, 1995;García-Martín et al, 2001) and cytokinin application increased apex elongation of germinating cork oak somatic embryos (González-Benito et al, 2002;Hernández et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, embryo dormancy and immaturity problems needed to be overcome. Osmoticum (high sucrose concentration) and chilling treatments had been tested in order to promote germination of cork oak somatic embryos (Fernández-Guijarro et al, 1995;García-Martín et al, 2001) and cytokinin application increased apex elongation of germinating cork oak somatic embryos (González-Benito et al, 2002;Hernández et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Somatic embryos of cork oak (Quercus suber L.) produce secondary embryogenesis on medium that lacks plant growth regulators (PGRs) (El Maâ taoui et al 1990;Ferná ndez-Guijarro et al 1995). This phenomenon, known as autoembryony, has been described for several species and is the basis of embryo cloning, giving this technique the potential to produce high multiplication rates (Merkle 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts were made since then to manipulate physical conditions in order to promote the adequate accumulation of reserves (Fernandes, 2011;. Fernández-Guijarro et al (1995) reported that somatic embryos from cork oak young seedlings increased maturation under light followed by storage at 4 °C, and that controlled starvation could benefit synchronization.…”
Section: Quercus Suber In Vitro Cloning: a Reliable Protocol?mentioning
confidence: 99%